Twelve owls - Erickson, Laura, 1951- (University of Minnesota Press, 2011)
Meet the saw-whet, the tiniest of Minnesota's owls, a mere eight inches from the tip of its blunt tail to the top of its rounded head. The simplest way to find one is to listen for the scolding calls of a flock of agitated chickadees. Or, if you're lucky, you might witness the male throwing all caution to the wind and "co-co-co-co-ing" for a mate, inching forward on every note like the bird in a cuckoo clock. From this fetching little creature to the magnificent great gray, the owls of Minnesota have found the perfect spokeswoman in this book, which is as charming as it is informativ.